A Critique of the Notions of Law and Ethics as Regulatory Systems for Healthcare - Izunwa, M. O. (2016)
Law and ethics are in their very natures, regulatory instruments and/or control mechanisms, for the proper direction of society towards the common good. While ethics as a system of moral values recommends what ought to be done or avoided, law commands the observance of those acts to be done and prohibits their contraries. Hence, ethics belongs to the internal morality of law and also operates as the justification for the precept of law. Working in a synergy, both act as social control mechanisms directive of the transactions in the social institutions and among them. The purpose of this entry is to make a general appraisal of the concepts of law and ethics especially as it relates to their correlation in the regulation of healthcare delivery system in Nigeria. In the emerging discourse, the method of hermeneutics is largely used especially in its dimensions of analysis and synthesis. It is the finding of this entry that law and ethics are two aspects of the same realitywhich regulates the affairs of men in society. The next discovery made by this paper is that the authentic ideas of lawand ethicsmeet at the venue of natural law.Hence, law+ethic =Natural Law. It is strongly recommended that the natural law theory of legality and morality be upheld in all jurisdictions as the applicable directive theory and practice of law and ethics especially with regard to the healthcare delivery system.